Modelo geométrico e cinemático dos aquíferos do município de Abaetetuba com vista aos aspectos hidrogeológicos - NASCIMENTO, Juliana Carolina Santos do (2019)
The present work sought to study in an integrated way the hydrogeological and neotectonic aspects of the Abaetetuba region, northeast of the State of Pará, aiming to contribute to the knowledge of the aquifers system from the determination of parameters of geometric geological and kinematic aspects and the relation between them. The database to reach the scope of work involved the analysis of information contained in the IBGE planialtimetric chart, in Geoeye images and landsat 8 satellite, in digital elevation models of SRTM - Shuttle Radar Topographic Mission - (resolution 90 m and 30 m) and Alos Palsar (resolution 30 m and 12 m), in constructive profiles of wells and in the SIARGAS database, which were systematized and integrated in a GIS - Geographic Information System - developed specifically for this work. From these data, the main characteristics of the drainage network and relief were analyzed, in order to determine the influence of neotectonic processes on the current configuration of these elements. The drainage maps were made in the ArcMap 10.5 software, based on vector data provided by the IBGE - Brazilian Institute of Geography and Statistics- , refined with the use of Geoeye image and landsat 8. Relief maps were generated from MDE - Digital Elevation Model - the radar image treatment was performed in the Global Mapper software v19, and the layout in ArcMap, except for the hypsometric map, in which QGis 3.4 software was used. The results of the integrated analysis point to the presence of a structural domain with sinistral characteristics with occurrence of NW-SE normal faults, NESW transcurrent and E-W transtensives. These structures modified the geometric aspects of the aquifers of the region, and possibly modified the underground water flow pattern, in addition to defining a recharge area (traction structures) for deeper reservoirs.